VD_FINDINFO HC / 2013 / 566 vom 5. September 2013 - VD Tribunal cantonal (2013)
DROIT D'EMPTION, ANNOTATION, REGISTRE FONCIER, MESURE PROVISIONNELLE, POUVOIR DE DISPOSER, DÉPENS | 959 CC, 960 al. 1 ch. 1 CC, 960 al. 2 CC, 961 al. 1 ch. 2 CC, 971 al. 1 CC, 972 al. 1 CC, 972 al. 2 CC, 47 al. 1 ORF, 89 al. 3 ORF, 261 al. 1 CPC (CH), 262 let. b CPC (CH), 265 al. 1 CPC (CH), 265 al. 2 CPC (CH), 315 al. 4 CPC (CH), 315 al. 5 CPC (CH), 20 TDC, 3 TDC, 6 TDC